Pemaafan Pada Etnis Jawa Ditinjau dari Faktor Demografi - H. Fuad Nashori; Tb. Zulrizka Iskandar; Kusdwiratri Setiono; A. Gimmy Prathama Siswadi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
This study examined the forgiveness related to demographic factors such as: age, gender, and education level. The subjects were 335 who are yogyakarta city residents (Java), Moslem, male andfemale, aged teens, early adulthood, middle adult, elderly, which were selected using stratified random cluster sampling technique. Instruments using the forgiveness scale compiled by researchers. Analysis of data using mean difference test (t-test) and ANOVA . The results showed: (a) there is no difference in forgiveness between men and women, (b) there is no difference in forgiveness between adolescence, ear It adults, middle adults, and the elderly, and (c) there is a difference in forgiveness, the education variable. Forgiveness on Higher Education is a higher education than forgiveness on SMP /MTs and SMA /SMK/MAKeywords: forgiveness, age, sex, level of education